Improved solid phase extraction for selective and efficient quantification of sunset yellow in different food samples using a novel molecularly imprinted polymer reinforced by Fe3O4@UiO-66-NH2 - Hatamluyi, Behnaz; Sadeghian, Reihaneh; Malek, Farhad; Boroushaki, Mohammad Taher (Food chemistry, 2021)
•Successful preparation of a novel molecularly imprinted polymer reinforced by Fe3O4@UIO-66-NH2 nanocomposite was presented.•Combination of Fe3O4@UIO-66-NH2 and MIP technique exhibited excellent selectivity and high efficiency.•Application in different food samples were successful. The overuse of synthetic dyes in food products has gradually increased in recent years, resulting food safety and human health has become a global issue. An innovative design of a magnetic molecularly imprinted polymer (Fe3O4@UiO-66-NH2@MIP) for efficient, fast, and selective determination of sunset yellow (SY) from different food products was described in this study. The absorption properties of Fe3O4@UiO-66-NH2@MIP were elucidated by adsorption kinetics, isotherms, reusability, and selectivity experiments. Because of the incorporation of porous Fe3O4@UiO-66-NH2nanocomposite into molecularly imprinted polymer an efficient nanosorbent with a short equilibrium time, a high adsorption capacity, and a good imprinting factor was finally obtained. The porous Fe3O4@UiO-66-NH2@MIP are also used for quantification of the SY. Under optimal conditions, good linearity (R2 0.9964) in the range of 1.0–120 mg L−1 and a low limit of detection (0.41 mg L−1) was observed with satisfactory recoveries (92.50–106.1%) and excellent reusability (RSD ≤ 6.6% after 12 cycles).